Handwashing sinks as reservoirs of carbapenem-resistant Acinetobacter baumannii in the intensive care unit: a prospective multicenter study - Wei, Li; Feng, Yu; Lin, Ji; Kang, Xia; Zhuang, Hongdi; Wen, Hongxia; Ran, Shasha; Zheng, Lan; Zhang, Yujing; Xiang, Qian; Liu, Yan; Wu, Xueqin; et al. (Frontiers in Public Health, 2024)
The extent to which sinks are contaminated by carbapenem-resistant Acinetobacter baumannii (CRAB) in intensive care units (ICUs) and the association between these contaminated sinks and hospital acquired CRAB infections during non-cluster period remains largely unknown. Here, we performed a prospective multicenter study in 16 ICUs at 11 tertiary hospitals in Chengdu, China, sampling sinks, collecting CRAB clinical isolates and conducting whole-genome sequencing and analysis. A total of 789 swabs were collected from 158 sinks, and 16 CRAB isolates were recovered from 16 sinks, resulting in a contamination rate of 10.16%. Twenty-seven clinical isolates were collected during the study period. The majority (97.67%, 42/43) of the CRAB isolates belonged to ST2 and 36 (83.72%) of them had both blaOXA-23 and blaOXA-66. The 43 strains belonged to 12 clones.One certain clone caused multiple contaminations of 7 sinks in one GICU. Two clones of ST2 blaOXA-23 and blaOXA-66-carrying sink strains were likely the sources of the two clusters in the two GICUs, respectively. Five ST2 blaOXA-23-carrying isolates were found to be a common clone but were recovered from two hospitals. The contamination rate of CRAB in handwashing sinks is high in some local ICUs, and the contaminated sinks can serve as environmental reservoirs for CRAB cluster.